Comparative effects of three different ventilatory treatments on arterial blood gas values and oxygen extraction in healthy anaesthetized dogs. (May 2022) - Boustead, Keagan J.; Grace, Justin F.; Buck, Roxanne K.; Zeiler, Gareth E.
Abstract: Objective: To compare the effect of invasive continuous positive airway pressure (CPAP), pressure-controlled ventilation (PCV) with positive end-expiratory pressure (PEEP) and spontaneous breathing (SB) on PaO2, PaCO2 and arterial to central venous oxygen content difference (CaO2 -CcvO2 ) in healthy anaesthetized dogs. Study design: Prospective randomized crossover study. Animals: A group of 15 adult male dogs undergoing elective orchidectomy. Methods: Dogs were anaesthetized [buprenorphine, medetomidine, propofol and isoflurane in an air oxygen (Fi O2 = 0.5)]. All ventilatory treatments (CPAP: 4 cmH2 O; PCV: 10 cmH2 O driving pressure; PEEP, 4 cmH2 O; respiratory rate of 10 breaths minute –1 and inspiratory-to-expiratory ratio of 1:2; SB: no pressure applied) were applied in a randomized order during the same anaesthetic. Arterial and central venous blood samples were collected immediately before the start and at 20 minutes after each treatment. Data were compared using a general linear mixed model ( p < 0.05). Results: Median PaO2 was significantly higher after PCV [222 mmHg (29.6 kPa)] than after CPAP [202 mmHg (26.9 kPa)] and SB [208 mmHg (27.7 kPa)] ( p < 0.001). Median PaCO2 was lower after PCV [48 mmHg (6.4 kPa)] than after CPAP [58 mmHg (7.7 kPa)] and SB [56 mmHg (7.5 kPa)] ( p < 0.001). Median CaO2 -CcvO2 was greater after PCV (4.36 mL dL –1 ) than after CPAP (3.41 mL dL –1 ) and SB (3.23 mL dL –1 ) ( p < 0.001). PaO2, PaCO2 and CaO2 -CcvO2 were no different between CPAP and SB ( p > 0.99, p  = 0.697 and p  = 0.922, respectively). Conclusions and clinical relevance: CPAP resulted in similar arterial oxygenation, CO2 elimination and tissue oxygen extraction to SB. PCV resulted in improved arterial oxygenation and CO2 elimination. Greater oxygen extraction occurred with PCV than with CPAP and SB, offsetting its advantage of improved arterial oxygenation. The benefit of invasive CPAP over SB in the healthy anaesthetized dog remains uncertain.